Analisis Pengaruh Influencer Terhadap Keputusan Pembelian Skincare dan Make Up di Kalangan GenZ - Alya Syafira Khairunnisa; Balqis Najmi Aqila Putri Syaela; Firda Nur Fauziah; Hasna Maisya Nazhirah; Myisha Azlia Nafhatus Sofa; Najma Silma Nayyara; Rama Wijaya Abdul Rozak (Lembaga Pengembangan Kinerja Dosen, 2024)
This research analyzes the influence of influencers on purchasing decisions for skincare and makeup products among Generation Z. Data was collected through a questionnaire distributed to 170 respondents. The results show that most of Generation Z follows influencers' social media accounts to obtain product information and recommendations. Influencer reviews have a significant influence on purchasing decisions, with 85.9% of respondents being interested in buying products after seeing influencer reviews. However, 88.8% of respondents still conduct additional research before making a purchase. The presence of influencer reviews can trigger consumptive behavior, with 69.4% of respondents stating so. To overcome this behavior, 87.6% of respondents set a special budget, and 89.4% compare product prices. Nevertheless, 64.1% of respondents spent more than their planned budget, with 60.6% spending more than IDR 200,000 per month on skincare and makeup products. This research concludes that influencers have a significant influence in attracting purchase interest and purchasing decisions among Generation Z for skincare and makeup products.